Different responses of sedimentary δ15N to climatic changes and anthropogenic impacts in lakes across the Eastern margin of the Tibetan Plateau. (1st June 2016) - Xu, Hai; Yu, Keke; Lan, Jianghu; Sheng, Enguo; Liu, Bin; Ye, Yuanda; Hong, Bin; Wu, Huixian; Zhou, Kangen; Yeager, Kevin M.
Highlights: Historical changes in sed. δ 15 N in lakes across ETP areas are dominated by climatic changes. Atm. Nr deposition modifies recent 15 N trends in low lacustrine primary productivity (LPP) lakes. Changes in LPP dominate sed. δ 15 N trends in high LPP lakes. Abstract: Knowledge of historical variations in sedimentary δ 15 N values and their relation to modern ones in lakes is critical in understanding N cycling in inland aquatic systems. Here we present late Holocene sedimentary δ 15 N variations in four lakes across the Eastern margin of the Tibetan Plateau (ETP), namely Lake Qinghai and Lake Chaonaqiu over north ETP (N-ETP) area, and Lake Yihai and Lake Lugu over south ETP (S-ETP) area. The results show that: (1) during historical periods when anthropogenic forcing was weak, the centennial/multi-decadal changes in δ 15 N values were dominated by climatic changes. Higher precipitation brought greater nutrients supply and led to higher Lacustrine Primary Productivity (LPP) and higher δ 15 N values in lake sediments, and vice versa. (2) During the recent/modern epoch with enhanced anthropogenic impacts, sedimentary δ 15 N values in Lake Qinghai and Lake Chaonaqiu (mid-high latitude lakes with low LPP) showed decreasing trends, possibly related to the increased global atmospheric reactive nitrogen (Nr) deposition. On the contrary, sedimentary δ 15 N values in Lake Lugu and Lake Yihai (subtropical lakes with high LPP) showed increasing trends, most likely because more dissolved inorganic nitrogen in lake water was used during LPP processes. This study highlights that LPP plays an important role in modifying sedimentary δ 15 N values both for historical and modern times, whereas atmospheric Nr deposition seems to influence the modern/recent sedimentary δ 15 N trends in lakes with low LPP.